The complete mitogenome of purple mottled shore crab Cyclograpsus granulosus H. Milne-Edwards, 1853 (Crustacea: Decapoda: Grapsoidea). (1st November 2016) - Tan, Mun Hua; Gan, Han Ming; Lee, Yin Peng; Austin, Christopher M.
Abstract: The mitochondrial genome sequence of the purple mottled shore crab, Cyclograpsus granulosus, is documented (GenBank accession number: LN624373), which makes it the third for genera of the superfamily Grapsoidea. Cyclograpsus granulosus has a mitogenome of 16, 300 bp consisting of 13 protein-coding genes, two ribosomal subunit genes, 22 transfer RNAs and a non-coding AT-rich region. The base composition of the C. granulosus mitogenome is 36.15% for T, 19.54% for C, 33.14% for A and 11.17% for G, with an AT bias of 69.29%. The mitogenome gene order is atypical for the brachyuran crabs, but is identical to species of the genus Eriocheir from the same family.